The relationship between carotenoids and diabetic nephropathy: insights from NHANES - Wang, Lei; Feng, Tianpu; Tan, Ye; Zhang, Jue; Zhang, Ting; Huo, Juan; Song, XiaoXue; Lin, Xi; Li, Man; Liang, Wenxue; Ding, Qun (Frontiers in Nutrition, 2025)
ObjectiveDiabetic nephropathy (DN) poses significant health risks and imposes a substantial global disease burden. The association between carotenoid intake and DN remains unclear. Utilizing data from the 2007–2018 National Health and Nutrition Examination Survey (NHANES), this study investigates the relationship between multiple carotenoid subtypes and DN, aiming to inform exploratory insights for potential preventive strategies.MethodsThis cross-sectional analysis utilized NHANES 2007–2018 data with a multistage stratified sampling design. After a four-stage screening process, baseline participants were selected by excluding individuals with lacking diabetes-related data, pregnant women, and those with incomplete carotenoid intake or DN diagnostic records. Model 1 included 25,483 participants, while Model 2 comprised retained 13,271 participants after further adjustment for covariates (demographic characteristics, lifestyle factors, clinical indicators, and socioeconomic parameters). Dietary intake of six carotenoid subtypes (α-carotene, β-carotene, β-cryptoxanthin, Lycopene, Lutein, Zeaxanthin) was calculated using as the mean of two standardized 24-h dietary recalls. Type 2 diabetes mellitus (T2DM) was diagnosed based on fasting plasma glucose (≥126 mg/dL), HbA1c (≥6.5%), hypoglycemic medication use, or clinical diagnosis. DN was defined as a urinary albumin-to-creatinine ratio (UACR) ≥ 30 mg/g or estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m2 in T2DM patients. Statistical analyses employed weighted multivariable logistic regression using the R survey package, adjusting for sampling design and covariates. Associations were quantified as odds ratios (ORs per 10 μg/d carotenoid intake) with Benjamini-Hochberg correction for multiple comparisons. The significance threshold was set at α = 0.05.ResultsThis NHANES-based study revealed nonlinear associations between dietary carotenoids and diabetic nephropathy (DN) risk, with notable gender-and ethnicity-specific gender/ethnicity-specific effects. Univariate analysis demonstrated elevated DN risk with higher β-cryptoxanthin intake (OR = 1.413, 95% CI), though significance was attenuated dissipated after multivariable adjustment, suggesting confounding mediation by obesity and hypertension. Multivariable models identified threshold effects: the low α-carotene intake group exhibited a 75% reduced risk (OR = 0.25, 95% CI), while the high-intake group showed a paradoxical risk elevation (OR = 2.24, 95% CI). β-Carotene displayed gender-divergent effects, with the highest tertile significantly reducing risk in males by 43% (OR = 0.57, 95% CI). Interaction models highlighted intensified α-carotene protection in males and Non-Hispanic White (OR = 0.27–0.29), whereas lycopene correlated with a fivefold increased DN risk in Non-Hispanic Black (OR = 4.99, 95% CI). Cardinal risk factors included advanced age (OR = 1.06/year), obesity (OR = 1.07/BMI unit), male sex (OR = 3.05), and hypertension (OR = 4.7), while higher education (OR = 0.72) and moderate alcohol consumption exerted inversely associated effects. These findings underscore the necessity of integrating nutrient thresholds (e.g., α-carotene optimization) and social determinants into DN prevention, though racial subgroup analyses warrant validation through prospective cohorts due to sample size constraints.ConclusionClinicians managing DN should: Prioritize Consider α-carotene’s biphasic dose–response relationship, prioritizing intake within the optimal dosage window; Utilize Leverage β-carotene’s gender-specific benefits for male patients; Exercise caution in consider exploringing lycopene-rich dietary interventions diets for African American populations. Public health initiatives should incorporate nutrient-gender-ethnicity triadic assessments into DN education programs to advance precision nutrition guidelines.